Analysis of functional composition of avifauna of “Dniprovsko-Orilsky” Nature Reserve - Пономаренко, О. Л.; Онуфріїв, Р. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The article describes the modern state of avifauna of “Dniprovsko-Orilsky” Nature Reserve. Now the avifauna of the reserve comprises 185 bird species and consists predominantly of aquatic and wetland birds (41,62%). Forest (31,35%) and forest-edge birds (12,97%) are subdominant groups. For the last 8 years the list of bird fauna increased by 9 species. The basic tendency of change of avifauna of the reserve is diminishing the number of breeding species and rise of the number of migrant species and species which nest outside the reserve but use its territory as feeding grounds. The cause is in shallowing and overgrowing of reservoirs and degradation of streamside forests. Biotechnical measures can become the decision of this problem e.g. clearing of estuarine parts of channels and creation of new small islands and spits.